2006
DOI: 10.1007/s00467-006-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation in children with posterior urethral valves

Abstract: The objective of this study was to analyze whether renal transplantation (RT) in children with posterior urethral valves (PUV) constitutes a special group with respect to groups with different etiologies of end-stage renal disease (ESRD). Between 1979 and 2004, 22 RT were performed in 19 children with PUV. The median age at RT was 10 years (range: 1.3-17). Immunosuppression was provided by triple therapy and polyclonal/monoclonal antibodies. This group was compared with the two control groups: (1) glomerulopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Similar to previous studies, we found no significant difference in graft and patient survival rates between study patients and controls (3,5,6,8,9,16,21,32,33). Our 93% and 79% graft survival rates at 1 and 5 years posttransplant compare favorably with the 91% and 80% for LD KTx recipients as well as the 83% and 65% for deceased donor (DD) KTx recipients reported by the NAPRTCS (34).…”
Section: Khositseth Et Alsupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to previous studies, we found no significant difference in graft and patient survival rates between study patients and controls (3,5,6,8,9,16,21,32,33). Our 93% and 79% graft survival rates at 1 and 5 years posttransplant compare favorably with the 91% and 80% for LD KTx recipients as well as the 83% and 65% for deceased donor (DD) KTx recipients reported by the NAPRTCS (34).…”
Section: Khositseth Et Alsupporting
confidence: 89%
“…In our study, the patients with obstructive and reflux uropathy had a higher incidence of urinary obstruction, urinary reflux, urolithiasis and UTIs, as compared with matched controls. Our 45% incidence of urologic complications is higher than the 19-35% reported in the literature (5,9,12,17,21,27,28). We suspect this difference is, in part, due to our longer follow-up period and our use of a detailed data base.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations